2007
DOI: 10.2193/2005-720
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Wood Duck Ducklings and Broods in Mississippi and Alabama

Abstract: Although North American wood ducks (Aix sponsa) are well‐studied throughout their range, researchers know little about demographic and environmental factors influencing survival of ducklings and broods, which is necessary information for population management. We studied radiomarked female and duckling wood ducks that used nest boxes and palustrine wetlands at Noxubee National Wildlife Refuge (NNWR) in Mississippi, USA, in 1996–1999, and riverine wetlands of the Tennessee‐Tombigbee Rivers and Waterway (TTRW) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(63 citation statements)
references
References 50 publications
4
57
2
Order By: Relevance
“…Contrary to the southern breeding range, we did not find evidence of a relationship with hatch date or mass. Patterns in habitat selection were consistent with previous research that identified use of woody or dense vegetative cover (McGilvrey , Sousa and Farmer , Smith and Flake , Granfors and Flake , Davis et al ). Brood and duckling survival may limit recruitment at our northern study area and additional data collection is required to support life‐cycle analysis (Coluccy et al , Davis et al ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Contrary to the southern breeding range, we did not find evidence of a relationship with hatch date or mass. Patterns in habitat selection were consistent with previous research that identified use of woody or dense vegetative cover (McGilvrey , Sousa and Farmer , Smith and Flake , Granfors and Flake , Davis et al ). Brood and duckling survival may limit recruitment at our northern study area and additional data collection is required to support life‐cycle analysis (Coluccy et al , Davis et al ).…”
Section: Discussionsupporting
confidence: 88%
“…We assumed complete brood and duckling loss upon the death of a female during the brood‐rearing period (Granfors ). We defined a successful brood as ≥1 duckling surviving to 30 days post‐hatch (Granfors , Davis et al ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rigorous estimates of survival rates and understanding factors influencing those rates are critical for discerning proximate and ultimate causes of dynamics, regulation, and persistence of populations (Newton 2004; Ozgul et al 2006) and for devising and implementing management interventions for species conservation (Davis et al 2007). Population dynamics of many vertebrate species are strongly influenced by changes in survival rates (Heppell et al 2000; Oli and Dobson 2003; Stahl and Oli 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Brood survival of Ring-necked Ducks in Minnesota (0.235) was similar to other diving ducks in the boreal forest (e.g., 5 of 22 and 1 of 10 scaup broods to 30 days [Greater Scaup (Aythya marila) and Lesser Scaup combined] in each of 2 years; Walker and Lindberg 2005), but was low compared to dabbling ducks (Mallards: Talent et al 1983, Orthmeyer and Ball 1990, Stafford et al 2002Wood Ducks: Ball et al 1975, Davis et al 2007; and Gadwall [Mareca strepera]: Pietz et al 2003), and diving ducks in parkland habitats of Minnesota and Manitoba (Canvasbacks; Korschgen et al 1996b, Leonard et al 1996. Brood survival in Ring-necked Ducks has only been examined previously in Maine and was substantially higher there (77% to 45 days, n = 64; McAuley and Longcore 1988).…”
Section: K W I Devmentioning
confidence: 59%